Redesain Interior Ruang Inap untuk Kenyamanan Pasien di Rumah Singgah Kanker Samarinda: Redesigning Temporary Stay Room Interiors to Enhance Patient Comfort at the Samarinda Cancer Shelter - Hidayati, Zakiah; Putra, Hatta Musthafa Adham; Noviana, Mafazah; Latief, Oktavian Daroyni; Rahman, M. Haikal; Abdurrokhman, Abdurrokhman (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Samarinda Cancer Shelter is an essential facility for cancer patients from various regions in East Kalimantan. However, the interior design of the temporary stay room still has problems that affect patient comfort and accessibility. This community service activity aims to redesign the layout of the temporary stay room, which consists of patient resting rooms, companion rooms, and isolation rooms, considering the needs of patients and companions. The redesign involves adding a ramp to improve accessibility, using soundproofing materials, and utility systems such as air conditioning and blowers for better air quality. Adjustments were also made to the isolation room, such as improving toilet facilities, reducing bed capacity to one with the addition of comfort facilities, and choosing a soft color palette to create a calming atmosphere. The redesign results are expected to improve the comfort, function of the space, and quality of life of cancer patients and other residents. The intensive discussions with managers and users ensure that the proposed design solutions meet their needs.